Determination of certain thermo-physical properties of nanofluids - Lee, Poh Seng (2010)
The thesis is about the determination of certain thermo-physical properties of nanofluids. The properties of nanofluids at desired temperature, particle size and concentration can be estimated using the regression equations developed to evaluate the viscosity and thermal conductivity for water based nanofluids. No single equation is available in literature to determine the property of nanofluid at desired temperature, particle size and concentration. Besides, the experimental datas in the existing literature are in discrete manner. The experimental data published in literature is used to obtain regression equation valid for a wide range of operating conditions. Using FORTRAN program for regression analysis, the datas for viscosity and thermal conductivity of water base and nanofluids is used to obtain the regression coefficients. The different models such as Non-Linear regression, Least Square and Linear regression models are considered in the analysis for the determination of coefficients for parameters such as temperature, volume concentration and particle size for water and nanofluids. Finally the model which gives the lowest deviation is selected base on few aspects such as coefficient of equation, maximum and minimum deviation. A graph is plotted using Origin software. Properties of nanofluids can be estimated and the Prandt number can be calculated which will help determine the heat transfer coefficient without conducting any experiment for determining the properties of nanofluids